Kebijakan Pembatasan Internet di Indonesia: Perspektif Negara Hukum, Hak Asasi Manusia, dan Kajian Perbandingan - Rofi Wahanisa (The Constitutional Court of the Republic of Indonesia, 2021)
The rapid growth in internet use has led governments in various countries, including Indonesia, to implement “internet restriction policies” to offset the possibility of internet abuse. Such restrictions on the internet have caused polemics, especially regarding the rights to freedom of opinion and the right to communicate and seek or receive information. In this paper, the polemic will be explored further based on 3 (three) perspectives, among others: (1) the rule of law; (2) human rights; and (3) legal comparisons. This paper is written using the juridical-normative legal research method. The results of the analysis of this paper show that: (1) there are still unfulfilled principles of the rule of law in internet restrictions; (2) limitation of human rights in the limitation of “internet networks” by which do not have a legal basis; and (3) the expected characteristics of internet restrictions in the view of several countries, namely: a) there is a clear juridical basis; b) contains clear limitation procedures; c) inspection and supervision; d) there is an independent supervisor; e) there is a mechanism of protection, recovery, and rehabilitation for innocent parties.